#TITLE_ALTERNATIVE# - AIRLANGGA DHARMASANDIKA CAKRAWIJAYA (NIM : 10509036) PEMBIMBING : M. Abdulkadir Martoprawiro Ph.D;A,
Magnesium hydride is one of the promising metal hydrides materials that can be used as hydrogen storage media. Magnesium hydride has many advantages when used as a hydrogen storage media such as the ability of reversible usage, high energy density, and relatively inexpensive. However, the use of magnesium hydrides as hydrogen storage media still have some shortcomings, such as the temperature required to release hydrogen from the material is very high, which is about 300 Ã‚Â°C, as well as the relatively slow desorption kinetics. Some of these problems can be reduced with the addition of a catalyst . One of the catalysts that have been investigated for this system is the addition of the transition metal into the magnesium hydride systems. Some of the metals that have been reported succeeded in giving catalytic effect are Cr and Nb. With the addition of the transition metal, the temperature required by the magnesium hydride to decompose can be significantly reduced. Hydrogen desorption kinetics are also reported better. In this research, modeling of the addition of transition metals into the magnesium hydride systems was done. Modeling in the present study was not conducted through a solid-state approach or periodics, but through a molecul approach. The software used in this modeling is an open-source software NWChem with Avogadro visualization software . Modeling was carried out at various amount of magnesium atoms in the stable structure, which is obtained through geometry optimization. From the result of the modeling on the stable structure, hydrogen adsorption was modeled with closing down the hydrogen to a stable structure. Having obtain the result and paramaeter, the models remodeled with the addition of transition metals to see the effect of the addition of transition metals on magnesium hydride systems was also done. The result of the last modeling was to obtain the amount of energy required for hydrogen to be adsorped by magnesium. The best catalyst candidate obtained through this research was cromium. Altough niobium also gives a good catalytic effect, hydrogen adsorption energy needed by magnesium hydride catalyzed by cromium are lower than the one catalyzed by niobium.